Community-Based Local Wisdom Development : Strengthening Accounting and Production Management Skills “Batik Village New Normal Bogor” - Fredi Andria; Amelia Rahmi; Muhamad Sunarzi; Soleha Nuramanah; Anisa Intan Selatan; Salmah Salmah; Eneng Tita Tosida; Prihastuti Harsani (Research Collaboration Community (RCC), 2022)
Batik art which is an intangible cultural heritage native to Indonesia that can be developed based on the potential of local wisdom in each region. This activity is aimed at increasing the ability and providing understanding to the local community-based batik MSME group in managing simple finances and optimal production management. The method used in this activity is theoretical and concept training which is carried out face-to-face, mentoring and direct monitoring in the field by the resource persons. This activity is targeted to be able to increase the 2 (two) new normal batik business groups that have just been formed, able to implement an appropriate and good bookkeeping system in the operation of their business. And can also run an effective and efficient production management system, so as to be able to produce good batik products and have a competitive advantage compared to batik products that are already on the market.